Fundamentals of Computation Theory 17th International Symposium, FCT 2009, Wroclaw, Poland, September 2-4, 2009, Proceedings - Kutylowski, Miroslaw; Gebala, Maciej; Charatonik, Witold (Theoretical Computer Science and General Issues, 2009)
This book constitutes the refereed proceedings of the 17th International Symposium Fundamentals of Computation Theory, FCT 2009, held in Wroclaw, Poland in August 2009. The 29 revised full papers were carefully reviewed and selected from 67 submissions. The papers address all current topics in computation theory such as automata and formal languages, design and analysis of algorithms, computational and structural complexity, semantics, logic, algebra and categories in computer science, circuits and networks, learning theory, specification and verification, parallel and distributed systems, concurrency theory, cryptography and cryptograhic protocols, approximation and randomized algorithms, computational geometry, quantum computation and information, bio-inspired computation.